The Larva of Spaniocercoides hudsoni Kimmins (Plecoptera: Notonemouridae) from New Zealand - McLellan, Ian (Illiesia, 2005)
The larva of Spaniocercoides hudsoni is described for the first time, notes are given on habitat and distribution of the species is shown.
Keywords: insekti; Plecoptera; vrbnice; Nova Zelandija